2015
DOI: 10.1007/s11249-015-0483-8
|View full text |Cite
|
Sign up to set email alerts
|

Reply to the Comment by Scott Bair, Philippe Vergne, Punit Kumar, Gerhard Poll, Ivan Krupka, Martin Hartl, Wassim Habchi, Roland Larson on “History, Origins and Prediction of Elastohydrodynamic Friction” by Spikes and Jie in Tribology Letters

Abstract: Bair, accompanied by some of his past co-authors, has Commented on our paper "History, Origins and Prediction of Elastohydrodynamic Friction"We believe that our paper presents a balanced summary of current understanding of EHD friction, its origins and prediction. However Bair et al. appear to have chosen to interpret our paper as an assault on the high stress viscometric approach that Bair has championed for some years and also as an espousal of the Eyring model of rheology which he has consistently denigrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…High-pressure viscometers can reach shear rates of only ~ 10 4 s −1 at EHL pressures (> 1 GPa) for low-viscosity fluids before shear heating becomes uncontrollable [15]. At similar pressures, tribometer experiments under thin-film EHL conditions can reach much higher shear rates (10 6 s −1 ) before shear heating becomes excessive [16], but it has been debated how useful the rheological data from such experiments are to predict EHL friction [3][4][5]. On the other hand, non-equilibrium molecular dynamics (NEMD) simulations are ideally suited to study the rheology of fluids at high shear rates, since thermostats can be used to suppress shear heating.…”
Section: Shear Thinningmentioning
confidence: 99%
See 1 more Smart Citation
“…High-pressure viscometers can reach shear rates of only ~ 10 4 s −1 at EHL pressures (> 1 GPa) for low-viscosity fluids before shear heating becomes uncontrollable [15]. At similar pressures, tribometer experiments under thin-film EHL conditions can reach much higher shear rates (10 6 s −1 ) before shear heating becomes excessive [16], but it has been debated how useful the rheological data from such experiments are to predict EHL friction [3][4][5]. On the other hand, non-equilibrium molecular dynamics (NEMD) simulations are ideally suited to study the rheology of fluids at high shear rates, since thermostats can be used to suppress shear heating.…”
Section: Shear Thinningmentioning
confidence: 99%
“…Numerical methods, analytical solutions, and experimental techniques have all advanced significantly over the last few decades [2]. However, the measurement and prediction of EHL friction remains a significant challenge and continues to attract much controversy [3][4][5]. In addition to the aforementioned methods, molecular dynamics (MD) simulations have emerged as tools capable of giving unique insights into the nanoscale behaviour of lubricants, including under EHL conditions [6].…”
Section: Introductionmentioning
confidence: 99%
“…41 The subject has been extensively analysed by Bair and it is currently a subject of heated debate. 4244…”
Section: Discussionmentioning
confidence: 99%
“…41 The subject has been extensively analysed by Bair and it is currently a subject of heated debate. [42][43][44] It is also found that such predictions depend on an accurate description of the local pressure-viscosity coefficient, , which can only be predicted from high pressure viscometer measurements. This type of rheometer is not commercially available and therefore few lubricants have been characterised by research centres up to the pressure levels encountered in EHL contacts.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, researchers dealing with high pressure rheometry are advocating a Carreau based model [4]. Several articles that heated up the debate were published in 2014 and 2015 by Spikes and Jie [4,5], Bair and his co-authors [6], and it seems that there is still no consensus on this topic.…”
Section: Introductionmentioning
confidence: 99%